2011
DOI: 10.3113/fai.2011.0422
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Analysis of a Tensioned Suture Device in the Fixation of the Ligamentous Lisfranc Injury

Abstract: Abduction stress may be valuable when diagnosing and testing the transverse ligamentous Lisfranc injury. Both suture-button and screw fixation methods restrain motion at the Lisfranc complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…In some cases an injured ligament may occur, but it is difficult to predict. 21 Ligament rupture is often repaired by scar tissue, which has poor tensile resistance as well as wear resistance, and can easily cause ligament re-rupture and makes the joint unstable. 22 So our patients were treated with hollow screws inserted from the medial cuneiform to the second metatarsal bone base and another one inserted from the fifth metatarsal base to the cuboid, to enhance the strength of the Lisfranc ligament and to maintain the anatomical reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases an injured ligament may occur, but it is difficult to predict. 21 Ligament rupture is often repaired by scar tissue, which has poor tensile resistance as well as wear resistance, and can easily cause ligament re-rupture and makes the joint unstable. 22 So our patients were treated with hollow screws inserted from the medial cuneiform to the second metatarsal bone base and another one inserted from the fifth metatarsal base to the cuboid, to enhance the strength of the Lisfranc ligament and to maintain the anatomical reduction.…”
Section: Discussionmentioning
confidence: 99%
“…9,47,48 Recent studies have confirmed equivalent stability across the Lisfranc joint when using a suture button device as compared with screw fixation. 49,50 Even so, suture button devices should be used with extreme caution, as multi-plane instability cannot be adequately stabilized with flexible fixation. If any instability in the sagittal plane is noted on preoperative or intraoperative imaging, the authors recommend a screw for fixation after reduction of the Lisfranc complex.…”
Section: Surgical Hardwarementioning
confidence: 99%
“…10 These injuries are 3 dimensional requiring stabilization not only to prevent widening but to address rotation as well. 12,13 Adding a second TightRope to the construct adds stability by addressing rotation and medial-lateral compression. 9,11 Biomechanical cadaveric comparisons of screw versus single TightRope fixation have shown conflicting results.…”
Section: Historical Perspectivementioning
confidence: 99%